PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF UNTUK MENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUKSI DARI KERTAS KORAN BEKAS SISWA KELAS IV SDN 003 TANJUNG KECAMATAN KOTO KAMPAR HULU - Putrapi, Anren Putrapi; Marhadi, Hendri Marhadi; ', Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : Problem in this research is still its doily skill of student in study of art in course of study of teacher still use the way of conventional, that is: student less involved in study process, more teacher use discourse method, even  do  not use study model, learn only from teaching materials or teacher, process its  his its  heedless study empirically student, so that mentioned cause student keterampilam become to lower. Pursuant to the problems hence require to look for  by  its resolving road;street by using hand in glove model  of  its bearing empirically student in everyday life, and all important can make atmosphere learn productive and creative. Subjek in this research  is  class student of IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu with amount of student 19 people. This research  is   done conducted  in two cycle, cycle of I executed  by  thrice cycle and meeting of II  is  also  done conducted   by  thrice meeting. Instrument data collecting  at  this research  is  observation sheet learn and student. This research in the form of Research Of Action Class ( PTK), this research aim to to increase skill make class student construction object of IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu. Result of this research  of  menunjukan that strategy study of kreatif-produktif can uplift skill student in making construction object. This matter can be seen from average value which increasing.  At  elementary score  of  mean assess student that is 57,32 and  at  cycle of I become 66,23 experiencing of the make-up of with difference 8,91 poin. While mean result of learning student  at  cycle of II that is 76,61 experiencing of the make-up of with difference 10,38 poin. This  of  its meaning  of  strategy study of kreatif-produktif can uplift skill to make object of kontruksi of newspaper paper of is ex- class student IV SD N 003 Tanjung Kecamatan Koto Kampar Hulu. Keyword : Creative Strategy Study - Productive, Skill, Object Construction